The Effects of Ecologic Condition on Antimicrobial Activity of Endemic Herbal Extracts in Fars Province - Abdorasoul Zakerin; Elaheh Ahmadi; Mehdi Fasihi-Ramandi; Sara Abdollahi; Alireza Molazadeh; Somayeh Jafari; Ghader Allahverdi; Seyed Amin Kouhpayeh; Mohammad Hasan Meshkibaf (Fasa University of Medical Sciences, 2015)
Background & Objectives: Ecologic conditions affect production of effective pharmaceutical products. We evaluate the effect of ecologic conditions on antibacterial effects of herbal plants in Fars.   Materials & Methods: We collected eight plant species including Trachyspermum copticum, Withania somnifera, Laurus nobilis, Carum carvi, Thymus, Rosemary, Zataria multiflora, and Lavandula in Fasa and Sepidan.. Their antibacterial effects were studied by disk diffusion method, well assay method, and Minimum Inhibitory Concentration (MIC). Ecological and weather conditions were derived from internet.   Results: Comparing with standard antibacterial indexes the following results were achieved. Fasa herbs including Trachyspermum copticum, Zataria multiflora, Laurus nobilis, and Rosemary had the most effect on Staphylococcus aureus, while Carum carvi had the least effect. This effect in Sepidan herbs was the most in Trachyspermum copticum, Zataria multiflora, and Rosemary, while Carum carvi had the least effect. Surveying the effects against E.coli among Fasa herbs, Zataria multiflora had the most and Carum carvi and Lavandula had the least effects. On the other hand, among Sepidan herbs, Trachyspermum had the highest and Carum carvi, Lavandula, and Laurus nobilis had the lowest effects on E.coli. Antibacterial effects of Fasa herbs against Pseudomonas aeruginosa was the most in Zataria multiflora and Thymus and the least in Carum carvi. In Sepidan herbs, it was the highest in Zataria multiflora and the lowest in Carum carvi. Conclusion: Considering the differences in antibacterial effects of the herbs in two ecologic conditions, we suggest other researchers to pay attention to the mentioned effects in their studies.